Inducible CD40 expression mediates NFκB activation and cytokine secretion in human colonic fibroblasts. Issue 10 (11th September 2003) - Gelbmann, C M; Leeb, S N; Vogl, D; Maendel, M; Herfarth, H; Schölmerich, J; Falk, W; Rogler, G
Abstract : Background: CD40 has been shown to be a functional activation antigen on a variety of cell types involved in immune responses. As intestinal fibroblasts and myofibroblasts may play a role during mucosal inflammation, we investigated the functional consequences of CD40 induction in primary cultures of human colonic fibroblasts. Methods: Primary colonic lamina propria fibroblasts (PCLF) were isolated from endoscopic biopsies and surgical specimens. Cultures were used between passages 3 and 9. CD40 surface display was determined by FACS analysis and mRNA expression by reverse transcription-polymerase chain reaction. Secretion of cytokines was determined by ELISA. Nuclear factor κB (NFκB) activation was shown by electrophoretic mobility shift assay (EMSA). Results: After priming with interferon γ (IFN-γ) (200 U/ml) for 72 hours, five of eight tested PCLF cultures showed induction of CD40 surface display (up to 10-fold). Induction of CD40 mRNA expression was demonstrated by semiquantitative polymerase chain reaction. In the responder-PCLF cultures, IFN-γ alone caused a 1.5–5-fold increase in interleukin (IL)-8 secretion. Addition of 1 ng/ml CD40L was sufficient to achieve a further increase in IL-8, IL-6, or monocyte chemotactic protein 1 (MCP-1) secretion (2.5–18-fold of controls). Incubation with CD40L alone without priming with IFN-γ had no effect. The proteasome inhibitor N -acetyl-leucinyl-leucinyl-norleucinal (ALLN 100 µM) reduced IFN-γ/CD40L mediated cytokine induction, suggesting participation of NFκB, which was directly demonstrated by EMSA. CD4+ T cells induced MCP-1 secretion by PCLF, which was prevented by addition of an excess of CD40-IgG fusion protein. CD40 expression on PCLF could also be demonstrated in vivo by immunohistochemistry. Conclusion: The CD40-CD40L pathway augments mucosal inflammatory responses via mucosal PCLF. CD40-CD40L mediated T cell/PCLF interactions could play an important role during intestinal mucosal inflammation.